An Overview of Agricultural Pollution in Vietnam : The Aquaculture Sector - Cong, Nguyen Van (World Bank, Washington, DC, 2018)
Aquaculture is an important and growing part of Vietnam’s agricultural economy. The aquaculture industry’s expansion has, however, contributed to environmental degradation and become a potential threat to the industry’s sustainability. Aquaculture expansion has involved the conversion of large areas, including mangroves, to farms and ponds, leading to changes in ecosystems and land use. In addition, aquaculture practices generate an array of emissions, most of them carried in wastewater and solid waste. This report is meant to provide a broad national overview of pollution problems in the aquaculture subsector. It aims to describe the nature, magnitude, and drivers of aquaculture pollution problems, taking stock of the state of evidence on this topic. It also touches upon current responses to the problem and offers a number of directions for policymakers.